Inhibition of HIV-1 Replication by Secondary Metabolites From Endophytic Fungi of Desert Plants - Wellensiek, Brian P. (Bentham Open, 2013)
Most antiretroviral drugs currently in use to treat an HIV-1 infection are chemically synthesized and lead to the development of viral resistance, as well as cause severe toxicities. However, a largely unexplored source for HIV-1 drug discovery is endophytic fungi that live in a symbiotic relationship with plants. These fungi produce biologically active secondary metabolites, which are natural products that are beneficial to the host. We prepared several hundred extracts from endophytic fungi of desert plants and evaluated the inhibitory effects on HIV-1 replication of those extracts that showed less than 30% cytotoxicity in T-lymphocytes. Those extracts that inhibited viral replication were fractionated in order to isolate the compounds responsible for activity. Multiple rounds of fractionation and antiviral evaluation lead to the identification of four compounds, which almost completely impede HIV-1 replication. These studies demonstrate that metabolites from endophytic fungi of desert plants can serve as a viable source for identifying potent inhibitors of HIV-1 replication.